Penggunaan Visual Dalam Percakapan Bahasa Inggris Di LKP Royal Skill Training Center - Akmal Akmal; Abdul Karim Syahputra; Rian Barialdi; Eben Ezer Sinaga (Smart Education, 2021)
Abstract: This training is a means or facility for students who are studying at LKP Royal Skill Training center in Tanjung Balai City to understand how they develop speaking skills in English using visual media. The visual media used is YouTube which is related to basic material in speaking skills. The students were asked to watch and understand what the actors and actresses were talking about on YouTube. The students were asked to provide comments on the topics they talked about then they made up the conversations they had watched. Keywords: Visual; Speaking ability; Youtube. Abstrak: Pelatihan ini merupakan sarana bagi para peserta didik atau siswa yang sedang belajar di LKP Royal Skill Training Center di Kota Tanjung Balai untuk memahami bagaimana mereka mengembangkan kemampuan berbicara dalam Bahasa Inggris dengan menggunakan media visual. Media visual yang digunakan adalah youtube yang berkaitan dengan materi dasar dalam kemampuan berbicara. Para peserta didik diminta untuk menonton dan memahami apa yang dibicarakan para aktor dan aktris dalam youtube tersebut. Para peserta didik diminta untuk memberikan komentar tentang topik yang mereka bicarakan kemudian mereka membuat percakapan yang telah mereka tonton. Kata Kunci: Visual; Kemampuan berbicara; Youtube.